Housing for Survival : insecurity of tenure, property loss and domestic violence against women in Recife - BERNARDINO, Raquel Ludermir (2021)
Domestic violence against women is a devastating problem and yet, while its consequences for housing have been well documented, the residential scenarios where it occurs remain underexplored. Thisthesis exploresthe intersections between domestic violence against women and housing challenges – before, during and after abuse – with a particular focus on insecurity of tenure and property loss. Using a feminist grounded theory, the thesis examines the housing trajectories of 56 low-income women interviewed in a domestic violence court and in three selected settlements in Recife, Brazil. Additional data coming from document review and interviews with 28 key-informants allow triangulation and provide insights into the disjuncture between legal and policy frameworks and women’s lived experiences. Findings reveal that, even before domestic violence occurs, material and socially constructed disparities based on gender shape the residential scenarios where domestic violence takes place, weakening women’s de facto and perceived property rights, despite formal equality, leaving them more vulnerable to evictions and dispossession than men. During abusive relationships, these disparities combined with gaps between law and practice may expose women to a crucial dilemma: tolerating domestic violence in exchange for a place to live or not to lose property, or fleeing their homes to survive cyclic and escalating violence. The thesis introduces two concepts: “trade-offs for shelter”, made by survivors who lack housing alternatives to escape abuse, and “gender violence evictions”, encompassing the specific form of insecurity of tenure provoked by domestic violence. After leaving abusive relationships, while public policies fail to address their basic housing needs, survivors and their children are often pushed into a housing deficit, and are likely to face new or persistent cycles of abuse, housing insecurity and inadequacy, effects that can transmit disadvantages across generations. The thesis also addresses “patrimonial violence against women”, a specific form of domestic violence legally recognized in Brazil, but sometimes exercised in a seemingly non-violent manner. Findings reveal how women are likely to lose their rightful share of property upon separation and inheritance, while their attempts to claim and exercise property rights can trigger or aggravate gender violence. Despite legal recognition, patrimonial violence against women remains poorly recognized by survivors and neglected in police and courts, contributing to the reproduction of gender inequalities and women’s subordination to men. Findings also reveal contradictory outcomes of tenure regularization and housing policies that, even when claiming to empower, can disadvantage women by silencing accounts of violence, trapping women in abuse, and triggering violent backlash. The thesis contributes to the debate on housing in domestic violence contexts by considering, beyond the consequences of abuse, the gender disparities that permeate the housing processes that precede and intertwine with violence. It also draws attention to the explicit housing deficit provoked by domestic violence, as well as a “hidden” housing deficit encompassing women unable to leave abusive relationships when lacking alternative housing. Addressing the immediate and longitudinal effects of domestic violence to women’s housing and assets portfolios is a crucial step towards the realization of gender equality and freedom from violence.